Research on the extension method of the main signal source of the synchrotron radiation device - Zhang Kai; Wei Yelong; Chen Qiuju; Wu Congfeng; Pang Jian; Tang Yungai; Du Baiting; Zhang Shancai; Feng Guangyao (Dianzi Jishu Yingyong, 2024)
The main signal source is one of the key components of the synchrotron radiation device. It is not only used to generate the highly stable reference signals required by each subsystem of the synchrotron radiation light source, but also used to generate the high-precision working clock required by the control system of the entire device. Generally, one RF signal source is used as the main signal source. But the commercial RF signal source generally has only one output channel, which is far from meeting the needs of the synchrotron radiation device, while the use of traditional power splitters to expand the main signal channel also suffers from amplitude attenuation, accuracy degradation, and inconsistent phase. In order to solve the above problem, the method of extending one channel output of microwave signal source with RF shortcut chip AD9361 has been proposed in the paper.